Sindrom MELAS: Kelainan Genetik Mitokondria - Muhamad Fathurrahman Zain; Kevin Jeremia Purba; Delisa Mutiara Nabila; Takhfa Nur Asyifa; Rani Himayani (Medula, 2023)
MELAS (mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes) is an inherited mitochondrial genetic disorder. Paternal mitochondria are present only in the sperm tailpiece due to a mutation in the tRNA in the mitochondrial gene MTTL1. MELAS is the most common mitochondrial disease with an incidence prevalence of 1 in 4000. MELAS syndrome is a multi-organ disease with a wide variety of manifestations including stroke-like episodes, dementia, epilepsy, lactic acidosis, myopathy, recurrent headaches, hearing loss, diabetes, and short stature. Individuals with the MELAS syndrome often present with more than one initial clinical manifestation. The diagnosis can be made with Hirano’s criteria for MELAS. The diagnostic criteria for MELAS must include the following events: (1) signs of encephalopathy, often with dementia and seizures, (2) episodes similiar to stroke (stroke-like episodes) in young age, and (3) biochemical evidence of mitochondrial dysfunction such as lactic acidosis or RRF in muscle biopsy. There is no specific treatment for MELAS syndrome, but most of the treatment for MELAS is symptomatic and involves multidiscipline such as neurologists, cardiologists, endocrinologists, audiologists, ophthalmologists, physical and occupational therapy and psychology, considering that MELAS syndrome can cause dysfunction of several organ.